Evaluation of milk replacers containing new protein soruces and a probiotic - Morrill, J.L; Laster, J.F.; Morrill, J.M.; Feyerherm, A.M. (Kansas Agricultural Experiment Station, 2011)
The objectives of this experiment were to evaluate bovine and porcine plasma proteins as sources of protein for calf milk replacers and to evaluate a commercial probiotic. Four replacers were compared; an all milk protein control, two replacers with 25% of protein from bovine plasma protein or porcine plasma protein, and a replacer identical to the control except that it contained a probiotic (Biomate FG, Chr. Hansen's Laboratory) instead of antibiotic. The 120 bull calves (7 ± 3 days of age) were divided into four equal groups, and calves from each group were fed 4 quarts per day of one of the replacers until weaned and all of a commercial starter they would eat. For the control, porcine plasma, bovine plasma, and probiotic replacer groups, respectively, during the 6-wk period, the weight gains were 23.8, 29.5, 27.9, and 22.2 lb. Starter consumptions were 53.7, 67.8, 58.7, and 54.6 lb, respectively. Deaths were 2, 1, 3, and 0, respectively. Increases in wither height were similar among diets. Increases in weight gains and starter consumed by calves fed the plasma proteins compared to controls approached significance (P = .10); differences between control and probiotic replacer groups were not significant.
Keywords: Milk replacers; Calves; Plasma proteins; Probiotics